Utilising Reflective Practice Groups as pedagogy in ordination training and theological development - Gubi, Peter Madsen (Practical theology, 2019)
With the Church of England's ([2014. Formation Criteria with Mapped Selection Criteria for Ordained Ministry in the Church of England. https://www.churchofengland.org/media/2139103/formationcriteriaforordainedministryapprovedhofbpsdec2014.docx]) recent formation criteria now requiring ordinands to have a greater degree of reflexive capability, this article considers the pedagogy of Reflective Practice Groups in ordination training and focuses on how reflexivity can be developed in a group context, towards fostering greater spiritual formation, theological reflection, self-awareness, relational practices for pastoral encounter, resilience and self-care practices for ministry. Some foci for reflexivity' are advocated for use within Reflective Practice Groups in ordination training.